A lithium ion battery
By using the non-aqueous electrolyte and the complex of the compound of structural formula 1 with the silicon element in the lithium-ion battery, the problems of gas bloating and impedance growth during the circulation of the lithium-ion battery are solved, and the circulation performance and safety are significantly improved.
Patent Information
- Application Number
- CN202110392819.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-04-13
AI Technical Summary
Lithium-ion batteries have problems with gas bloating and impedance growth during the circulation process, resulting in deterioration of circulation performance and safety hazards.
Non-aqueous electrolyte is used, and the negative electrode active material contains 2% to 50% silicon-based material, and a specific compound of structural formula 1 is added to the electrolyte. Through the complexation of the compound with the silicon element, an interface film is formed to inhibit the volume effect. and improve cycle performance.
It significantly improves the problems of circulating gas bloating and impedance increase of the battery, improves the retention rate of circulation capacity, reduces gas production, and improves the circulating performance of the battery.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital devices and new energy vehicles due to their high energy density, long cycle life, low self-discharge rate, and green environmental protection. In order to improve the energy density of lithium-ion batteries, one of the directions is to use high-energy-density negative electrode active materials. Among them, silicon-based negative electrode materials have become an important direction for improving the energy density of lithium-ion batteries because of their high theoretical specific capacity (4200mAh / g), which far exceeds the theoretical specific capacity of graphite negative electrodes (372mAh / g). However, there is a large volume effect (≥300%) in the silicon-based negative electrode during the cycle process, which causes the solid electrolyte interface film on the surface of the silicon-based negative electrode to continuously break and regenerate during the battery cycle, resulting in the consumption of electrolyte and the loss of active lithium, and the increase of interface impedance, thereby deteriorating the cycle performance. At the same time, during the charging and discharging process of lithium-ion batteries, a large amount of reducing gas will be generated due to side reactions, causing the battery to swell, sharply deteriorating the cycle performance, and when the gas inside the battery accumulates to a certain extent, it may cause the battery to explode, and it will also bring safety hazards.
[0003] Therefore, it is necessary to provide a lithium-ion battery having a graphite and silicon-based composite material as a negative electrode, and the non-aqueous electrolyte used can effectively improve the gas expansion and impedance growth of the lithium-ion battery during the cycle, thereby improving the cycle performance of the battery. Summary of the invention
[0004] The technical problem solved by the present invention is to solve the problems of gas expansion, impedance growth and the like in the existing lithium ion batteries during the cycle process, thereby providing a lithium ion battery with excellent cycle performance.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material, and the silicon element in the silicon-based material accounts for 2% to 50% of the mass percentage of the negative electrode active material;
[0007] The non-aqueous electrolyte includes a solvent, an electrolyte salt and an additive, wherein the additive includes at least one of the compounds shown in Structural Formula 1:
[0008] ADBEC
[0009] Structural formula 1
[0010] wherein A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group;
[0011] D and E are each independently selected from a single bond, or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond;
[0012] Based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by the structural formula 1 is 0.01 to 5.0%.
[0013] Optionally, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups independently contained in A, B and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups of A, B and C is less than or equal to 10.
[0014] Optionally, A and C are each independently selected from the group shown in Structural Formula 2:
[0015]
[0016] wherein n is an integer selected from 0 to 4, R1 is selected from hydrogen, halogen, C1 to C5 hydrocarbon group or halogenated hydrocarbon group; R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C3 hydrocarbon group, C1 to C3 alkoxy group, oxygen atom, At least one of R2, R3, and R4 is selected from At least one of R2, R3, and R4 is selected from an oxygen atom, and at least one of R5, R6, and R7 is selected from And at least one of R5, R6 and R7 is selected from oxygen atoms.
[0017] Optionally, B is selected from the group shown in structural formula 3:
[0018]
[0019] Wherein, m is selected from an integer of 1 to 4, R8, R9, R 10 Each independently selected from a C1-C3 alkylene group, a C1-C3 alkoxy group, an oxygen atom, R8, R9, R 10 At least one selected from And R8, R9, R 10 At least one of them is selected from oxygen atoms.
[0020] Optionally, D and E are each independently selected from the group shown in structural formula 4:
[0021]
[0022] Wherein, z is selected from an integer of 0 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from single bonds,
[0023] Optionally, D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group;
[0024] Optionally, when A, B or C is substituted, the substituent is selected from halogen, hydrocarbon group or halogenated hydrocarbon group. More preferably, when A, B or C is substituted, the substituent is selected from halogen, alkyl group or halogenated alkyl group.
[0025] Optionally, A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.
[0026] Optionally, the compound represented by structural formula 1 is selected from one or more of the following compounds:
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034] Optionally, the mass percentage of silicon in the negative electrode active material is T%, and the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte is W%. The above substances satisfy the following conditions:
[0035] 2≤T≤10, and 0.01≤W≤3; or 10<T≤50, and 0.05≤W≤5.
[0036] Optionally, the silicon-based material is selected from at least one of silicon materials, silicon oxides, silicon-carbon composite materials and silicon alloy materials.
[0037] According to the lithium ion battery provided by the present invention, a silicon-based material is used as the negative electrode material, and a lithium ion battery with high energy density can be prepared. On the basis of the silicon-based negative electrode material, by adding the compound shown in structural formula 1 to the electrolyte, not only the energy density can be improved, but also the problems of battery cycle gas expansion and impedance increase can be significantly improved, the generation of gas during the battery cycle can be reduced, and the cycle capacity can be significantly improved. The inventors have found through a large number of experiments that the battery cycle performance does not improve linearly with the increase of the content of the compound shown in structural formula 1. The improvement of the battery performance by the compound shown in structural formula 1 is related to the mass ratio of silicon element to the negative electrode active material. When the mass ratio of silicon element to the negative electrode active material is 2% to 50%, and the addition amount of the compound shown in structural formula 1 is 0.01 to 5.0%, the battery cycle performance is significantly improved. DETAILED DESCRIPTION
[0038] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] The embodiment of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material, and the silicon element in the silicon-based material accounts for 2% to 50% by mass of the negative electrode active material;
[0040] The non-aqueous electrolyte includes a solvent, an electrolyte salt and an additive, wherein the additive includes at least one of the compounds shown in Structural Formula 1:
[0041] ADBEC
[0042] Structural formula 1
[0043] wherein A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group;
[0044] D and E are each independently selected from a single bond, or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond;
[0045] Based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by the structural formula 1 is 0.01 to 5.0%.
[0046] According to the lithium ion battery provided by the present invention, on the basis of silicon-based negative electrode materials, by adding the compound shown in structural formula 1 to the non-aqueous electrolyte, not only a high energy density lithium ion battery can be prepared, but also the problems of battery cycle gas expansion and impedance increase can be significantly improved, the generation of gas during the battery cycle can be reduced, and the cycle capacity can be significantly improved; however, it is difficult to play a good improvement role in other battery systems. The inventors have found through a large number of experiments that the battery cycle performance does not improve linearly with the increase of the content of the compound shown in structural formula 1. The improvement of the battery performance by the compound shown in structural formula 1 is related to the mass ratio of silicon element to the negative electrode active material. When the mass ratio of silicon element to the negative electrode active material is 2% to 50%, and the addition amount of the compound shown in structural formula 1 is 0.01 to 5.0%, the battery performance is significantly improved.
[0047] Regarding the relationship between the compound shown in structural formula 1 and the silicon element in the negative electrode active material, when the silicon content is between 2% and 50%, the compound shown in structural formula 1 is applied to the silicon-based negative electrode battery. During the battery formation process, the additive undergoes reduction decomposition on the surface of the silicon-based negative electrode to form an interface film. The organic components in the interface film are complexed with the silicon element in a certain proportion, which effectively inhibits the volume effect of the silicon-containing negative electrode during the charge and discharge process, improves the cycle bloating, and significantly improves the cycle capacity. When the silicon content is greater than 50%, adding the compound shown in structural formula 1 does not effectively improve the cycle. The reasons are as follows: due to the high silicon content, adding a small amount of the additive cannot form a complete complex and dense interface film during the formation process, the protection of the silicon-based material is insufficient, and the high-temperature cycle performance of the battery is basically not improved; while adding a large amount of the additive will cause the interface film of the negative electrode interface to be locally too thick, the impedance of the battery is seriously increased, and the lithium insertion and extraction is uneven, which also cannot effectively improve the cycle performance.
[0048] In some embodiments, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups or cyclic anhydride groups contained independently by A, B, and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups or cyclic anhydride groups of A, B, and C is less than or equal to 10.
[0049] In some embodiments, A and C are each independently selected from the group shown in Structural Formula 2:
[0050]
[0051] wherein n is an integer selected from 0 to 4, R1 is selected from hydrogen, halogen, C1 to C5 hydrocarbon group or halogenated hydrocarbon group; R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C3 hydrocarbon group, C1 to C3 alkoxy group, oxygen atom, At least one of R2, R3, and R4 is selected from At least one of R2, R3, and R4 is selected from an oxygen atom, and at least one of R5, R6, and R7 is selected from And at least one of R5, R6 and R7 is selected from oxygen atoms.
[0052] In a preferred embodiment, the combination of -R3-R2-R4- and the combination of -R7-R5-R6- are each independently selected from
[0053] In some embodiments, B is selected from the group shown in Structural Formula 3:
[0054]
[0055] Wherein, m is selected from an integer of 1 to 4, R8, R9, R 10 Each independently selected from a C1-C3 alkylene group, a C1-C3 alkoxy group, an oxygen atom, R8, R9, R 10 At least one selected from And R8, R9, R 10 At least one of them is selected from oxygen atoms.
[0056] In a preferred embodiment, -R9-R8-R 10 -The combination groups are each independently selected from
[0057] In some embodiments, D and E are each independently selected from the group shown in Structural Formula 4:
[0058]
[0059] Wherein, z is selected from an integer of 0 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from single bonds,
[0060] In some embodiments, A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.
[0061] In some embodiments, D and E are each independently selected from a single bond or a C1-C5 alkylene group, A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, cyclic sulfate group, cyclic sulfite group, cyclic sulfonate group, cyclic sulfone group, cyclic sulfoxide group, cyclic carboxylate group, or cyclic anhydride group, and when A, B, or C is substituted, the substituent is selected from a halogen, an alkyl group, or a haloalkyl group.
[0062] As an example, the compound represented by structural formula 1 can be selected from one or more of the following compounds:
[0063]
[0064]
[0065]
[0066]
[0067] In some embodiments, D and E are each independently selected from the group shown in Structural Formula 4:
[0068]
[0069] Wherein, z is selected from an integer of 1 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from
[0070] A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; preferably, when A, B or C is substituted, the substituent is selected from a halogen, a hydrocarbon group, or a halogenated hydrocarbon group, and more preferably, when A, B or C is substituted, the substituent is selected from a halogen, an alkyl group, or a halogenated alkyl group.
[0071] As an example, the compound represented by structural formula 1 can be selected from one or more of the following compounds:
[0072]
[0073]
[0074]
[0075] In some embodiments, the compound represented by structural formula 1 may also be selected from one or more of the following compounds:
[0076]
[0077]
[0078] It should be noted that the above are some of the compounds claimed to be protected by the present invention, but are not limited thereto and should not be construed as limiting the present invention.
[0079] A person skilled in the art, knowing the structural formula of the compound shown in Structural Formula 1, can know the preparation method of the above compound according to the common knowledge in the field of chemical synthesis. For example:
[0080] Compound 1-1 can be prepared by the following method:
[0081] Sorbitol, dimethyl carbonate, methanol, alkaline substance catalyst potassium hydroxide and organic solvent such as DMF are placed in a reaction container, and reacted under heating conditions for several hours, and then a certain amount of oxalic acid is added to adjust the pH to neutral. After filtering and recrystallization, intermediate product 1 can be obtained. Then, intermediate product 1, carbonate, dichlorothionyl, etc. are subjected to esterification reaction under high temperature conditions to obtain intermediate product 2, and intermediate product 2 is oxidized using an oxidant such as sodium periodate to obtain compound 1-1.
[0082] Compound 1-2 can be prepared by the following method:
[0083] After diacetone-D-mannitol, dimethyl carbonate, methanol, potassium carbonate and dioxane are reacted under heating and stirring for several hours, a certain amount of oxalic acid is added to adjust the pH of the solution to neutral, and the intermediate product 3 is obtained after filtering and concentration; an appropriate amount of pure water, carbonate, acid, etc. are added to the intermediate product 3 for hydrolysis reaction to obtain the intermediate product 4; then the intermediate product 4, dichlorothionyl and carbonate solvent are prepared under heating conditions to obtain the intermediate product 5; finally, the intermediate product 5 is oxidized using an oxidant such as sodium periodate to obtain compound 1-2.
[0084] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the compound represented by structural formula 1 is 0.01% to 5.0%. Specifically, the amount of the compound represented by structural formula 1 can be 0.01%, 0.02%, 0.05%, 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, or 5.0%.
[0085] When the amount of the compound shown in the structural formula 1 added is too small, it cannot play a protective film-forming role and the improvement effect on the battery performance is not obvious; when the amount of the compound shown in the structural formula 1 added is too much, the interface film formed at the negative electrode interface is too thick, which is not conducive to the shuttling of lithium ions, and the cycle performance is deteriorated. Therefore, adding an appropriate amount of the compound shown in the structural formula 1 can improve the cycle performance of the battery.
[0086] In some embodiments, the additive further comprises at least one of an unsaturated cyclic carbonate compound, a fluorinated cyclic carbonate compound, a sultone compound, lithium difluorophosphate, vinyl sulfate (DTD), and lithium bis(fluorosulfonyl)imide (LiFSI);
[0087] In some embodiments, the unsaturated cyclic carbonate compound includes at least one of vinylene carbonate (VC) and vinyl ethylene carbonate (VEC); the fluorinated cyclic carbonate compound includes fluoroethylene carbonate (FEC); and the sultone compound is selected from at least one of 1,3-propane sultone (PS), 1,4-butane sultone (BS), and 1,3-propylene sultone (PST).
[0088] In some embodiments, based on the total mass of the lithium ion battery non-aqueous electrolyte as 100%, the content of unsaturated cyclic carbonate compounds is 0.1-5%; the content of fluorinated cyclic carbonate compounds is 0.1-30%; the mass percentage of sultone compounds is 0.1-5%; the mass percentage of lithium difluorophosphate is 0.1-2%; the mass percentage of vinyl sulfate (DTD) is 0.1-5%; the mass percentage of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.1-5%.
[0089] In some embodiments, the solvent includes one or more of an ether solvent, a nitrile solvent, a carbonate solvent, and a carboxylate solvent.
[0090] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, and the cyclic ether may be, but is not limited to, one or more of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but is not limited to, one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), and diethylene glycol dimethyl ether (TEGDME). The nitrile solvent may be, but is not limited to, one or more of acetonitrile, glutaronitrile, and malononitrile. Carbonate solvents include cyclic carbonates or chain carbonates. The cyclic carbonates may be, but are not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonates may be, but are not limited to, one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). The carboxylate solvents may be, but are not limited to, one or more of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.
[0091] In some embodiments, the electrolyte salt includes one or more of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt, and an aluminum salt.
[0092] In a preferred embodiment, the electrolyte salt is selected from a lithium salt. In a more preferred embodiment, the lithium salt includes one or more of LiPF6, LiBF4, LiBOB, LiDFOB, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, and LiN(SO2F)2.
[0093] In some embodiments, the concentration of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / L-8 mol / L. In a preferred embodiment, the concentration of the electrolyte salt in the non-aqueous electrolyte is 0.5 mol / L-4 mol / L. Specifically, the concentration of the electrolyte salt can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L.
[0094] In some embodiments, the positive electrode includes a positive electrode active material that can reversibly embed / de-embed metal ions (lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, aluminum ions, etc.). Preferably, the positive electrode active material is selected from at least one of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, LiFePO4, LiCoO2, LiMnO2, LiNiMnO2 and their composites.
[0095] In some embodiments, the mass percentage of silicon in the negative electrode active material is T%, and the mass percentage of the compound represented by Structural Formula 1 in the non-aqueous electrolyte is W%, and the above substances satisfy the following conditions:
[0096] When 2≤T≤10, preferably 0.01≤W≤3; or when 10<T≤50, preferably 0.05≤W≤5.
[0097] According to the research and verification by the inventors, when the mass percentage of silicon in the negative electrode active material is between 2% and 10%, adding an appropriate amount of electrolyte containing 0.01% to 3% of the compound of structural formula 1 can effectively improve the high temperature cycle performance of the battery, while when the addition amount is 3% to 5%, the impedance increases due to the interface film formed by the compound of structural formula 1, and the cycle performance decreases. When the mass percentage of silicon in the negative electrode material increases to between 10% and 50%, the optimal content of the compound of structural formula 1 required to form a complete interface film increases, so when the compound content is 0.05% to 5%, the cycle performance of the battery can be effectively improved.
[0098] In some embodiments, the silicon-based material is selected from at least one of a silicon material, a silicon oxide, a silicon-carbon composite material, and a silicon alloy material.
[0099] In some embodiments, the battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0100] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an organic-inorganic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0101] In some embodiments, the mass percentage of silicon in the negative electrode active material is 2% to 50%. Specifically, the mass percentage of silicon in the negative electrode active material can be 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%.
[0102] When the silicon content is between 2% and 50%, the compound shown in structural formula 1 is applied to a silicon-based negative electrode battery. During the battery formation process, the compound shown in structural formula 1 undergoes reduction decomposition on the surface of the silicon-based negative electrode to form an interface film. The organic components in the interface film are complexed with silicon elements in a certain proportion, which effectively inhibits the volume effect of the silicon-containing negative electrode during the charge and discharge process, improves the cycle bloating, and significantly improves the cycle capacity. When the silicon content is greater than 50%, the addition of the compound shown in structural formula 1 cannot effectively improve the cycle. The reasons are speculated as follows: due to the high silicon content, a small amount of the compound shown in structural formula 1 cannot form a complete complex and dense interface film during the formation process, and the protection of the silicon-based material is insufficient, and the high-temperature cycle performance of the battery is basically not improved; while the addition of a large amount of the compound shown in structural formula 1 will cause the interface film of the negative electrode interface to be locally too thick, the impedance of the battery is seriously increased, and the lithium insertion and extraction are uneven, which also cannot effectively improve the cycle performance.
[0103] The present invention is further described below by way of examples.
[0104] 1. Examples 1 to 62 and Comparative Examples 1 to 17
[0105] 1) Preparation of electrolyte
[0106] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and then additives were added according to the tables. The amount of additives used was calculated as a percentage of the total mass of the electrolyte.
[0107] 2) Preparation of positive electrode
[0108] The positive electrode active material LiNi was mixed in a mass ratio of 93:4:3 0.5 Co0.2 Mn 0.3 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive electrode plate with a thickness of 120-150μm.
[0109] 3) Preparation of negative electrode plate
[0110] The negative electrode active material SiO-C (graphite: silicon = 9:1), conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and the nickel lead wire is welded with an ultrasonic welder to obtain the negative electrode plate, and the thickness of the plate is 120-150μm.
[0111] 4) Preparation of battery cells
[0112] A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.
[0113] 5) Battery filling and formation
[0114] In a glove box with water and oxygen contents below 20 ppm and 50 ppm respectively, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left at 45°C for 24 h.
[0115] Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 min, 0.1C constant current charging for 180 min, 0.2C constant current charging for 120 min, aging at 45°C for 48 h, secondary vacuum sealing, and then further charging to 4.4 V at 0.2C constant current, and discharging to 2.75 V at 0.2C constant current.
[0116] Performance Testing
[0117] 1. The lithium ion batteries prepared in the above-mentioned Examples 1 to 62 and Comparative Examples 1 to 17 were subjected to the following performance tests: High temperature cycle performance test
[0118] The prepared lithium-ion battery was placed in a constant temperature oven at 45°C and charged to 4.4V (LiNi 0.5 Co 0.2 Mn0.3 O2 / SiO-C), then charge at constant current and constant voltage until the current drops to 0.05C, then discharge at a constant current of 1C to 2.75V, and repeat this cycle. Record the discharge capacity and impedance of the first cycle and the discharge capacity and impedance of the last cycle, and measure the initial battery volume and the volume after 800 cycles.
[0119] The capacity retention rate, impedance growth rate and gas expansion rate of high temperature cycle are calculated as follows:
[0120] Capacity retention rate = discharge capacity of the last cycle / first cycle capacity × 100%;
[0121] Impedance growth rate = (impedance of the last circle - impedance of the first circle) / impedance of the first circle × 100%;
[0122] Swelling ratio = (battery volume after cycling - initial battery volume) / initial battery volume x 100%.
[0123] 1.1. The test results obtained in Examples 1 to 23 and Comparative Examples 1 to 12 are entered in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] From the test results in Table 1, it can be seen that when the mass percentage of silicon in the negative electrode active material is 2-50%, and the compound shown in Structural Formula 1 is used as an additive and its addition amount is 0.01-5.0%, the capacity retention rate of the battery is greatly improved compared with the case where the compound shown in Structural Formula 1 is not added, and the impedance growth rate and the gas expansion rate are significantly reduced. This shows that adding the compound shown in Structural Formula 1 to the non-aqueous electrolyte can play a good role in improving the cycle performance of the battery in a large range. From Comparative Examples 1-4, it can be seen that when the mass percentage of silicon in the negative electrode active material is 2-50%, the battery capacity without adding the compound shown in Structural Formula 1 is greatly reduced, and a drop occurs. The so-called drop refers to the nonlinear drop process of the discharge capacity of the lithium-ion battery during the cycle process, which is characterized by a large drop in the capacity of the battery in a short time. From Comparative Examples 5-12, it can be seen that when the mass percentage of silicon in the negative electrode active material is greater than 50%, even if 0.01-5.0% of the compound shown in Structural Formula 1 is added, the battery cycle performance is not improved.
[0128] At the same time, combined with the data of Examples 1-23, it is found that although the content of the compound represented by Structural Formula 1 is increasing, the improvement of the battery cycle performance is not linear, which means that the improvement of battery performance is not only related to the content of the compound represented by Structural Formula 1 but also to the mass percentage of silicon element in the negative electrode active material. Only when the contents of the two are coordinated within a certain range can the battery be significantly improved.
[0129] 1.2. The test results obtained in Examples 24 to 35 and Comparative Example 1 are entered in Table 2.
[0130] Table 2
[0131]
[0132] It can be seen from the test results in Table 2 that the mass percentage content (T%) of silicon element in the negative electrode active materials of Examples 24-29 is within the range of 2-10%, and the content of the compound shown in Structural Formula 1 is 0.01-3%. Although the mass percentage content (T%) of silicon element in the negative electrode active materials of Examples 30-35 is also within the range of 2-10%, the content of the compound shown in Structural Formula 1 is greater than 3%. The test results show that the minimum capacity retention rate of Examples 24-29 can reach 73.1%, while the maximum capacity retention rate of Examples 30-35 is only 75.1%, and the minimum capacity retention rate is only 63.6%. At the same time, the impedance growth rate and gas expansion rate of Examples 24-29 are generally lower than those of Examples 30-35. When the mass percentage of silicon in the negative electrode active material is between 2% and 10%, adding an appropriate amount of electrolyte containing 0.01% to 3% of the compound of structural formula 1 can effectively improve the high temperature cycle performance of the battery, while when the addition amount is 3% to 5%, the impedance increases due to the interface film formed by the compound of structural formula 1, and the cycle performance decreases. This shows that when the mass percentage (T%) of silicon in the negative electrode active material is 2 to 10%, and the content of the compound of structural formula 1 is 0.01 to 3%, it has a significant effect on improving the battery cycle performance.
[0133] 1.3. The test results obtained in Examples 11, 12, 36-44 and Comparative Example 13 are entered in Table 3.
[0134] Table 3
[0135]
[0136] It can be seen from the test results in Table 3 that the mass percentage (T%) of silicon element in the negative electrode active materials of Examples 11, 12, 36 to 39 is within the range of 10 to 50%, and the content of the compound shown in Structural Formula 1 is 0.05 to 5%. Although the mass percentage (T%) of silicon element in the negative electrode active materials of Examples 40 to 44 is also within the range of 10 to 50%, the content of the compound shown in Structural Formula 1 is less than 0.05%. The test results show that the capacity retention rates of Examples 11, 12, 36 to 39 after 800 cycles at 45°C are all above 70%, while the capacity retention rates of Examples 40 to 44 after 800 cycles at 45°C are all below 70%. At the same time, the impedance growth rate and the gas expansion rate of Examples 11, 12, 36 to 39 are about 20 percentage points lower than those of Examples 40 to 44. When the mass percentage of silicon in the negative electrode material increases to between 10% and 50%, the optimal content of the compound shown in structural formula 1 required to form a complete interface film increases, so when the compound content is 0.05% to 5%, the battery cycle performance can be effectively improved. This shows that when the mass percentage of silicon in the negative electrode active material is 10% < T ≤ 50%, the content of the compound shown in structural formula 1 is 0.05 to 5%, which significantly improves the impedance, gas expansion and cycle performance of the battery.
[0137] 1.4. The test results obtained in Examples 11, 45-58 and Comparative Examples 1-4 are entered in Table 4.
[0138] Table 4
[0139]
[0140] It can be seen from the test results in Table 4 that when the mass percentage of silicon in the negative electrode active material is 2-50%, the battery cycle performance is improved to varying degrees by adding compounds represented by different structural formulas 1 to the electrolyte.
[0141] 1.5. The test results obtained from Examples 59 to 62 and Comparative Examples 14 to 17 are entered in Table 5.
[0142] Table 5
[0143]
[0144] From the data in Table 5, it can be seen that in Examples 59 to 62, the compound represented by Structural Formula 1 is used in combination with conventional additives for lithium batteries, while Comparative Examples 14 to 17 do not add the compound represented by Structural Formula 1. The test results show that the capacity retention rate of Examples 59 to 62 after 800 cycles at 45°C is significantly higher than that of Comparative Examples 14 to 17, while the impedance growth rate and the flatulence rate are lower than those of Comparative Examples 14 to 17, indicating that the use of the compound represented by Structural Formula 1 in combination with conventional additives for lithium batteries can further improve the high temperature cycle performance of the battery.
[0145] In summary, the present invention can significantly improve the problems of battery cycle bloating and impedance increase by adding the compound shown in structural formula 1 to the non-aqueous electrolyte, reduce the generation of gas during the battery cycle, and maintain a significant improvement in the cycle capacity; at the same time, the inventor found through a large number of experiments that the battery performance does not improve linearly with the increase in the content of the compound shown in structural formula 1, and the improvement of the battery performance by the compound shown in structural formula 1 is related to the mass ratio of silicon element to the negative electrode active material. When the mass ratio of silicon element to the negative electrode active material is 2% to 50%, the compound shown in structural formula 1 can effectively improve the battery cycle performance. Further research found that when the mass percentage of silicon element in the negative electrode active material is 2% to 10%, and the content of the compound shown in structural formula 1 is 0.01% to 3%, it has a significant effect on improving the battery cycle performance; similarly, when the mass percentage of silicon element in the negative electrode active material is 10%<T≤50%, and the content of the compound shown in structural formula 1 is 0.05% to 5%, the battery bloating, impedance and cycle performance are significantly improved.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, characterized in that: The negative electrode includes a negative electrode active material, the negative electrode active material contains a silicon-based material, and the silicon element in the silicon-based material accounts for 2% to 50% by mass of the negative electrode active material; The non-aqueous electrolyte includes a solvent, an electrolyte salt and an additive, wherein the additive includes at least one of the compounds shown in Structural Formula 1: ADBEC Structural formula 1 wherein A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; D and E are each independently selected from a single bond, or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond; Based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by structural formula 1 is 0.01-5.0%; The mass percentage of silicon in the negative electrode active material is T%, and the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte is W%. The above substances satisfy the following conditions: 2≤T≤10, and 0.01≤W≤3; Or 10<T≤50, and 0.05≤W≤5.
2. The lithium-ion battery according to claim 1, characterized in that The number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups independently contained in A, B and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups of A, B and C is less than or equal to 10.
3. The lithium ion battery according to claim 1, characterized in that: A and C are each independently selected from the group shown in structural formula 2: Structural formula 2 wherein n is an integer selected from 0 to 4, R1 is selected from hydrogen, halogen, C1 to C5 hydrocarbon group or halogenated hydrocarbon group; R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C3 hydrocarbon group, C1 to C3 alkoxy group, oxygen atom, , or , at least one of R2, R3, and R4 is selected from , or , and at least one of R2, R3, and R4 is selected from an oxygen atom, and at least one of R5, R6, and R7 is selected from , or , and at least one of R5, R6, and R7 is selected from an oxygen atom.
4. The lithium-ion battery according to claim 1, characterized in that: B is selected from the group shown in structural formula 3: Structural formula 3 Wherein, m is selected from an integer of 1 to 4, R8, R9, R 10 Each independently selected from a C1-C3 alkylene group, a C1-C3 alkoxy group, an oxygen atom, , or , R8, R9, R 10 At least one selected from , or , and R8, R9, R 10 At least one of them is selected from oxygen atoms.
5. The lithium-ion battery according to claim 1, characterized in that: D and E are each independently selected from the group shown in structural formula 4: Structural formula 4 Wherein, z is selected from an integer of 0 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from single bonds, , , , , , , , , or .
6. The lithium-ion battery according to claim 1, characterized in that D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; Preferably, when A, B or C is substituted, the substituent is selected from halogen, hydrocarbon group or halogenated hydrocarbon group. More preferably, when A, B or C is substituted, the substituent is selected from halogen, alkyl group or halogenated alkyl group.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: A and C are identical to each other, A and B are identical to or different from each other, and D and E are identical to each other.
8. The lithium-ion battery according to claim 1, characterized in that The compound represented by structural formula 1 is selected from one or more of the following compounds: 。 9. The lithium-ion battery according to claim 1, characterized in that: The silicon-based material is selected from at least one of silicon oxide, silicon-carbon composite material and silicon alloy material.
Citation Information
Patent Citations
Silicon-carbon composite anode high-voltage lithium-ion battery
CN106299462A
Lithium ion battery electrolyte additive cyclic ethylene carbonate sulfate and preparation method thereof
CN111755753A